FACTORS AFFECTING STUDENTS’ PROBLEMS IN WRITING CAUSE AND EFFECT ESSAYS (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The purpose of this research was to investigate the factors affecting students’ problems in writing cause and effect essays at the third year of English department students of Bung Hatta University. The type of this research was qualitative and data were taken from twenty seven records of interview. The result of this research defected that there were several factors affecting students in writing cause and effect essays. They were interference of the first language (Bahasa Indonesia), the difficulties of English, lack of knowledge of writing components, intelligent Quotient (IQ), personality (mood and confidence), time allotted and lack of knowledge about general topics. The research finding implied that the students need to deepen their knowledge about the component of writing, especially a cause and effect essay since there are two ways to organize the idea in cause and effect essay; block and chain organization. Moreover, they are expected to read the current news or topics so as that they have prior knowledge when they are assigned to write as well as they are expected to write as often as possible so as that they produce better writing.